Physiological and transcriptomic analysis of Spartina alterniflora in response to imazapyr acid stress - Yaning Liu; Zhengmao Li; Lixia Li; Xiangyang Jiang; Chen Gao; Jiqiang Zhao (BMC Plant Biology)
Abstract As a key aspect of managing of invasive alien species in China, the prevention and control of Spartina alterniflora have become an important part of the work in coastal provinces, and imazapyr acid has been gradually applied in the control work due to its advantages of high efficiency and low toxicity. In this study, we applied 6.0 L/acre of 25% imazapyr acid aqueous stress treatment, and determined and analyzed the physiological activities and transcriptome profiles of S. alterniflora under sustained stress. Chlorophyll fluorescence was used as a technical tool to analyze the mechanism of photosynthesis and the photosynthetic physiological status of S. alterniflora. We analyzed the root system structure of S. alterniflora using a root system imaging system, and characterized the transcriptome of S. alterniflora by high-throughput sequencing technology. Specifically, after imazapyr acid exposure, the fluorescence imaging area of leaves were all decreased, and the fluorescence indexes such as Fv/Fm, Y(II) and PIabs were significantly decreased, while Y(NO) was significantly increased, and Y(NPQ) showed an increase followed by a decrease. Meanwhile, total root length, root surface area and biomass of S. alterniflora were suppressed after imazapyr acid exposure. In transcriptomic analysis, imazapyr acid inhibited the expression of genes involved in phenylpropanoid biosynthesis, nucleotide sugar-related metabolism, valine, leucine and isoleucine biosynthesis, and DNA replication in S. alterniflora. These results indicate that the effects of imazapyr acid stress on the leaves of S. alterniflora are heterogeneous, with the leaves initiating photoprotective mechanisms to ensure the normal functioning of the photosystem in the early stage of stress, and the PSII reaction centers being damaged in the late stage of stress, ultimately destroying the photosynthetic system. Meanwhile, imazapyr acid stress alters basic physiological processes such as metabolism and growth and development of S. alterniflora, thus affecting the growth and development of the plant root system, and ultimately leading to the death of S. alterniflora.